Design, synthesis and antifungal/anti‐oomycete activity of pyrazolyl oxime ethers as novel potential succinate dehydrogenase inhibitors. Issue 9 (5th May 2021) - Wang, Minlong; Du, Ying; Ling, Chen; Yang, Zhaokai; Jiang, Biaobiao; Duan, Hongxia; An, Jie; Li, Xinghai; Yang, Xinling
Abstract: BACKGROUND: Succinate dehydrogenase inhibitors (SDHIs) play an increasingly important role in controlling plant diseases. However, the similar structures of SDHIs result in rapid development of cross‐resistance development and a clear bottleneck of poor activity against oomycetes, therefore the need to seek new SDHI fungicides with novel structures is urgent. RESULTS: Innovative pyrazolyl oxime ethers were designed by replacing amide with oxime ether based on the succinate dehydrogenase (SDH) structure, and 19 pairs of Z ‐ and E ‐isomers were efficiently prepared for the discovery of SDHI compounds with a novel bridge. Their biological activities against four fungi and two oomycetes were evaluated, and substantial differences were observed between the Z ‐ and E ‐ isomers of the title compounds. Furthermore, most of these compounds exhibited remarkable activities against Rhizoctonia solani with EC50 values of less than 10 mg L −1 in vitro, and bioassay in vivo further confirmed that E ‐I‐6 exhibited good protective efficacy (76.12%) at 200 mg L −1 . In addition, Z‐I‐12 provided better activity against the oomycetes Pythium aphanidermatum and Phytophthora capsici (EC50 = 1.56 and 0.93 mg L −1 ) than those of boscalid. Moreover, E ‐I‐12 exhibited excellent SDH inhibition (IC50 = 0.21 mg L −1 ) thanks to its good binding ability to the SDH by hydrogen‐bonding interactions, π‐cation interaction and hydrophobic interactions. CONCLUSION: Novel pyrazolyl oxime ethers have the potential as SDHI compounds for future development, and the strategy of replacing an amide bond with oxime ether may offer an alternative option in SDHI fungicide discovery. Abstract : Thirty‐eight novel pyrazolyl oxime ethers composed of 19 pairs of Z ‐ and E ‐isomers were designed and synthesized for developing succinate dehydrogenase inhibitor fungicides with a novel bridge against phytopathogenic fungi and oomycetes. © 2021 Society of Chemical Industry.